Pakistan: A cost-benefit analysis of puddled planted rice vs. direct seeded rice - Rana, Abdul Wajid; Gill, Sitara; Akram, Iqra (International Food Policy Research Institute, 2024)
Rice-wheat, a major cropping system of Pakistan, is vulnerable to the negative impacts of climate change, manifesting in the form of yield reduction. Among various crops, rice is often identified as the most at-risk food crop which is prone to a substantial drop in yield because of climate change and weather variations. It is estimated that the yield of wheat and rice may decline by 14.7 percent and 20.5 percent, respectively, by 2050 due to changes in climate. It is expected that Pakistan could potentially incur a climate change-related loss of $19.5 billion by 2050 due to reduced wheat and rice crop yields due to water scarcity, rising average temperatures, and less precipitation. Research indicates that if current climate change patterns persist and farmers do not adopt suitable climate resilient methods, rice production in Pakistan could decline by as much as 36 percent by the year 2099.